Dead or alive? The federalism revolution and its meaning for public administration - Christensen, Robert K.; Wise, Charles R. (2009)
Federation jurisprudence shapes the powers that public administrators have to achieve policy priorities. Federalism, however, is neither static nor simplistic as a concept, and a proper understanding of the environment in which public administrators work rests on a careful analysis of US Supreme Court decisions. The authors review claims that a 2005 decision, Gonzales v. Raich, terminated a federalism revolution that had been ushered in a decade earlier. Does Raich in fact mark the end of the Supreme Court's federalism doctrine? Analysis of this question clarifies whether the past and current Court has articulated any direction touching on administrators' powers at both the national and state levels. The authors argue that before the federalism revolution is declared dead or alive, public administration can better understand the realities of the Supreme Court's doctrinal boundaries by examining a more detailed analysis of jurisprudence for what is says about the foundations of federalism such as the commerce clause, Fourteenth Amendment, Tenth Amendment, Eleventh Amendment, spending clause, and statutory interpretation issues. - Reproduced.
Keywords: Public administration; Federalism